2015
DOI: 10.1021/acs.chemrestox.5b00315
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Carboxylic Acid-Containing Drugs: The Role of Acyl Migration and CoA Conjugation Investigated

Abstract: Many carboxylic acid-containing drugs are associated with idiosyncratic drug toxicity (IDT), which may be caused by reactive acyl glucuronide metabolites. The rate of acyl migration has been earlier suggested as a predictor of acyl glucuronide reactivity. Additionally, acyl Coenzyme A (CoA) conjugates are known to be reactive. Here, 13 drugs with a carboxylic acid moiety were incubated with human liver microsomes to produce acyl glucuronide conjugates for the determination of acyl glucuronide half-lives by acy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 40 publications
1
57
1
Order By: Relevance
“…The reactivity of the acyl glucuronide conjugates of drugs and other xenobiotics has been studied extensively on account of their potential hepatotoxicity [1][2][3][4] (as have the corresponding S-acyl-CoA thioesters which are also chemically reactive). [5][6][7][8] Acyl glucuronides are formed through the conjugation of α-Dglucuronic acid with the carboxylic acid group of a xenobiotic in the presence of membrane-bound UDP-glucuronosyltransferase (UGT) enzymes. The 1-β-O-acyl glucuronides that form can undergo a cascade of spontaneous chemical reactions including acyl migration, anomerisation, and hydrolysis to produce seven further positional anomers: 1-α, 2-α, 2-β, 3-α, 3β, 4-α, 4-β, the aglycone, and both αand β-glucuronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of the acyl glucuronide conjugates of drugs and other xenobiotics has been studied extensively on account of their potential hepatotoxicity [1][2][3][4] (as have the corresponding S-acyl-CoA thioesters which are also chemically reactive). [5][6][7][8] Acyl glucuronides are formed through the conjugation of α-Dglucuronic acid with the carboxylic acid group of a xenobiotic in the presence of membrane-bound UDP-glucuronosyltransferase (UGT) enzymes. The 1-β-O-acyl glucuronides that form can undergo a cascade of spontaneous chemical reactions including acyl migration, anomerisation, and hydrolysis to produce seven further positional anomers: 1-α, 2-α, 2-β, 3-α, 3β, 4-α, 4-β, the aglycone, and both αand β-glucuronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…This might argue that the DNA damaging moiety is the intact lactone, and indeed a number of different lactones including AL have been shown to react with the DNA surrogate, 4-(p-nitrobenzyl)pyridine (Manso et al 2005;Fernández-Rodríguez et al 2007). However, lactones are hydrolysed by PON1 to the corresponding hydroxyl acid (Billecke et al 2000;Teiber et al 2003) and acyl glucuronides of carboxylic acid containing agents have been reported to be toxic and react with cellular macromolecules (Lassila et al 2015;Van Vleet et al 2017). The exact nature of the DNA damaging agent is thus currently unclear.…”
Section: Lactonementioning
confidence: 99%
“…In contrast to CBZ where the glucuronidation of the (di)hydroxylated metabolites involved the formation of an ether bond, transfer of glucuronic acid to the carboxyl group IBU molecule produced the acyl glucuronide (M382), i.e., an ester bond. The observation of a partially resolved peak cluster of M382 in the extracted ion chromatogram (m/z 381.1558) instead of a single peak with a defined retention time (see ESM Table S1) is typical of acyl glucuronides because they are subject to acyl migration yielding positional isomers [26]. Taking advantage of this characteristic behavior, the visual inspection of the peak profiles allowed to easily discriminate between the hydroxyglucuronides bearing the glucuronic acid on the OH group and the isobaric acyl glucuronides.…”
Section: Detection and Identification Of Drug Metabolitesmentioning
confidence: 99%